Information and communication technology (ICT) and economic growth nexus: A comparative global analysis - Muhammad Tariq Majeed; Tayba Ayub (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This paper analyzes the impact of diverse ICT indicators on economic growth at both global and regional levels. The analysis is based on a sample of 149 counties over the period 1980-2015. The empirical exercise is based on Ordinary Least Squares (OLS), Pooled OLS, Two Stage Least Squares (2SLS) and Generalized Method of Moments (GMM) techniques. The results show that all indicators of ICT accelerate both global and regional economic growth. However, some indicators such as online service, telecommunication infrastructure and e-government are comparatively more conducive in enhancing economic growth. The analysis for the subsamples of developed, emerging and developing countries reveal that emerging and developing countries are gaining more form ICT than developed countries, validating the argument that these economies are "leapfrogging" through ICT. Moreover, the Principal Component Analysis (PCA) of ICT indicators also confirms the results. Findings of the study are shown to be robust to different specifications, to alternative econometric techniques, to different control variables, and to regional sub-samples. This study contributes to the economic growth-ICT nexus by introducing the novel measures of ICT infrastructure such as telecommunication, online service and e-government index unlike previous literature that mainly emphasized the importance of fixed telephone and broadband subscriptions. Findings of the study imply that investment in ICT infrastructure is essential to take the maximum benefit from the knowledge economy of 21st century.
Keywords: 330; telecommunication infrastructure; e-government index; research and development; ICT infrastructure; SAARC; BRICS